Peran Kepala Sekolah sebagai Leader dalam Mengembangkan Budaya Sekolah - Miftahul Jannah; Yuyu Yuhana; Tatu Hilaiyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The school principal has an important role in building school culture. A school culture that is less effective in its implementation can reduce school performance and minimize the school's strategic management process, so that the school's vision and mission cannot be achieved. The success of an educational institution is determined not only by being supported by complete facilities and infrastructure, quality teachers and good student input, but school culture plays a role in increasing school effectiveness. The purpose of this research is to determine the role of the school principal as a leader in developing school culture. This research uses qualitative research methods. The two types of data used in this research are primary and secondary. This research collects data through observation, interviews and documentation. The data analysis used is data reduction, data presentation, and triangulation. The informants in this research were teachers and education staff. The research results show that the role of the principal as a leader can be seen from the culture created at SDN Ciwandan. SDN Ciwandan has a culture including welcoming new students with 7S (Smile, Greeting, Greeting, Polite, Polite, Greeting, Spirit), morning assembly, SEMUTLIS (Ten Minutes for a Healthy Environment), love of the Koran, SABSIH (Clean Saturday) , and Extracurricular. Building a school culture is not only the responsibility of the principal, all school members play an important role in building a good school culture.